Development of INSANG (Interaksi Sosial Anak Sekarang) Poster in Improving Social Skills - Qothrunnadaa Salsabila; Cucun Sunaengsih; Dadan Nugraha (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The decline in social interactions within the school environment has a significant impact on students' social skills. The purpose of this research is to enhance the importance of developing social skills among elementary school students in the digital era through a creative approach when creating a poster with the theme